Implementation of Internship Programs Enhances Graduate Employability: South African Context - Ngobeni, Tlangelani; Mahole, Ephraim; Nekhavhambe, Mutshutshu Michael (Indonesian Journal of Social Research (IJSR), 2025)
The South African government is grappling with youth unemployment and poverty, exacerbated by a lack of experience and skills required for job positions. The study explores the implementation of internship programs to enhance graduate employability, aiming to address South Africa's youth unemployment issue. Public Service has implemented internship programs to curb graduate unemployment, providing graduates with skills and experience to secure future employment. The study used a Mixed Research Method (MRM). Interviews and questionnaire data were collected concurrently from two different sample sizes. Quantitative data was analyzed using descriptive statistics, whereas qualitative data was analyzed using thematic analysis. The analysis found four main themes: experience, skills, unemployment, and job opportunity. A sample size of (N=190) participants from the Limpopo Department of Education. The study indicates that internships enhance graduate employability for interns after the program, primarily due to the acquired skills and experience. Forty-one (41%) of respondents believe that internship programs provide graduates with valuable work experience for employability. The study contributes to the existing literature and policymakers in the Limpopo Department of Education and other institutions by enhancing internship experiences and enhancing future job prospects through experiential learning theory. The Department should implement internship programs that positively impact graduates' employability. The study concludes that internships are vital in addressing youth unemployment and providing work experience for graduates.